Gender, health inequalities and welfare state regimes: a cross-national study of 13 European countries. Issue 1 (3rd September 2008) - Bambra, C; Pope, D; Swami, V; Stanistreet, D; Roskam, A; Kunst, A; Scott-Samuel, A
Abstract : Background: This study is the first to examine the relationship between gender and self-assessed health (SAH), and the extent to which this varies by socioeconomic position in different European welfare state regimes (Liberal, Corporatist, Social Democratic, Southern). Methods: The EUROTHINE harmonised data set (based on representative cross-sectional national health surveys conducted between 1998 and 2004) was used to analyse SAH differences by gender and socioeconomic position (educational rank) in different welfare states. The sample sizes ranged from 7124 (Germany) to 118 245 (Italy) and concerned the adult population (aged ⩾16 years). Results: Logistic regression analysis (adjusting for age) identified significant gender differences in SAH in nine European welfare states. In the UK (OR 0.88; 95% CI 0.78 to 0.99) and Finland (OR 0.85; 95% CI 0.77 to 0.95), men were significantly more likely to report "bad" or "very bad" health. In Denmark, Sweden, Norway, Holland, Italy, Spain and Portugal, a significantly higher proportion of women than men reported that their health was "bad" or "very bad". The increased risk of poor SAH experienced by women from these countries ranged from a 23% increase in Denmark (OR 1.23; 95% CI 1.08 to 1.39) to more than a twofold increase in Portugal (OR 2.01; 95% CI 1.87 to 2.15). For some countries (Italy, Portugal, Sweden), women's relatively worse SAH tended to be most prominent in the group with the highest level of education. Discussion: Women in the Social Democratic and Southern welfare states were more likely to report worse SAH than men. In the Corporatist countries, there were no gender differences in SAH. There was no consistent welfare state regime patterning for gender differences in SAH by socioeconomic position. These findings constitute a challenge to regime theory and comparative social epidemiology to engage more with issues of gender.